التكامل بين عمل المدقق الداخلي و المدقق الخارجي للحد من الفساد المالي: دراسة تطبيقية في جامعة الموصل - شيماء محمد سمير إبراهيم (PROSPECTIVE RESEARCHES, 2023)
Financial corruption is a serious phenomenon and a global issue that can be found all over the world, but its size and its forms and the degree of its spread varies from state to state. The growing manifestation of the problem of corruption today requires a pause with the audit profession, whether the audit in qustion was an internal audit or an external audit. Thus, the research seeks to clarify the concept and forms of financial corruption and expound the integration between the work of the internal auditor and external auditor in order to reduce corruption through the study applied to the activities and accounts of the presidency of the University of Mosul, during his presentation of the research problem in the "lack of integration between the work of the internal auditor and external auditor hich in turn leads to lack of the possibility of reducing of the violations and abuses in the activity of the university and the emergence of accounting errors as a result of fraud, manipulation, and thus the spread of corruption and serious material damage to public property". One of the main conclusions of the research is the integration between the work of the internal auditor and external auditor through a system of internal control and audit program and the financial statements by the reports prepared by both sides that contribute to the reduction of corruption.